181 Genes Involved in Platelet Activity and Thrombosis are Overexpressed in Human CD34+ Derived Megakaryocytes Driven to High Ploidy. (6th June 2015) - Choudry, Fizzah; Garcia, Sara; Downes, Kate; Kostadima, Myrto; Frontini, Mattia; Ouwehand, Willem; Martin, John; Mathur, Anthony
Abstract : Introduction: Mean platelet volume is increased in the setting of acute myocardial infarction (AMI) and is a poor prognostic marker despite antiplatelet use. The megakaryocyte (platelet precursor) that resides in the bone marrow has a mean physiological ploidy of 16n. Megakaryocyte size and DNA content are also shown to be increased in AMI. To investigate if megakaryocytes of higher ploidy are transcriptionally different and therefore have the ability to produce larger and more active platelets we performed RNA sequencing in megakaryocytes cultured with or without dimethylfasudil (diMF), an exogenous peptide that drives megakaryocyte ploidy further than previously documented by non-selective aurora kinase inhibition. Methods: Human adult blood CD34 + derived megakaryocytes from 4 individuals underwent 3 days of culture with or without 5 µM diMF. RNA from untreated and treated cells was sequenced and used for differential gene and transcript expression analysis. Results: Mean ploidy in the untreated megakaryocytes was 2n while diMF treatment drove mean ploidy to approximately 8n. This was associated with a morphological increase in size and nuclear multilobulation. Differential gene expression analysis revealed that in megakaryocytes that had been driven to high ploidy levels, 33 genes were downregulated while 65 genes underwent significant upregulation when compared with untreated megakaryocytes. Gene ontology analysis demonstrated that the downregulated genes were significantly enriched for transcripts involved in the cell cycle including CDC45, chromatin assembly factor 1β, and MCMs. In contrast, genes that were upregulated in higher ploidy megakaryocytes were significantly enriched for transcripts involved in haemostatic and coagulation pathways including VWF, coagulation factor XIII, thrombin receptor-like 2, PDGFβ, angiopoietin 1, thrombospondin 1 and plasminogen activator inhibitor type 1. Furthermore, glycoprotein IIIa (part of the fibrinogen/VWF receptor) and tubulin β1 (involved in microtubule changes in platelet release) were both significantly upregulated in higher ploidy megakaryocytes. Both of these genes are specific to megakaryocytes and platelets. Conclusion: This is the first analysis of megakaryocytes driven to high ploidy level in vitro using RNA sequencing. Our results demonstrate that along with the anticipated modulation of cell cycle genes with increasing ploidy, higher ploidy megakaryocytes significantly overexpress genes that are involved in megakaryocyte function, platelet activation and thrombosis. These results therefore support a role for platelet production from megakaryocytes of higher ploidy in thrombotic disease.